Estudo e desenvolvimento de um sistema baseado em jogos para gerenciamento e acompanhamento remoto de terapia para reabilitação motora - Menezes Júnior, Rômulo Costa de (2013)
Physical therapy treatment could take advantage of the use of information systems based games to encourage the practice of rehabilitation exercises and monitor therapy. The popularization of devices that capture the motion as Kinect fostered the development of such applications to interact with patients to physical rehabilitation systems, allowing to be used remotely.For these applications could help with physical therapy in the clinic or in the patient s home, remotely, they shall provide motivational characteristics to assist the patient in the correct execution of movements, be adaptable to the needs of patients and help diagnose during the evolution of the treatment. Thus, from research and comparative analysis of published studies, this study aimed to specify and develop the most important elements that a system for physical therapy should include, looking of a complete system-based games. This research resulted in the development of a prototype containing all the desirable characteristics that have been identified and may be used by physical therapists to assist in physical therapy. The features were developed and evaluated by experienced physical therapists from questionnaires to describe the user experience and possible additional needs. The trial and the results of the questionnaire revealed that the system was well accepted among therapists and already could be used to treat various diseases. However, it is still necessary to develop more playful elements in games, to improve motivation; make small corrections in mechanical motion detection and generate a report about the treatment evolution.